Effectively Handling Silence in Counseling Groups - Vriend, John; Dyer, Wayne W. (Canadian Journal of Counselling and Psychotherapy, 2012)
Periods of silence in counseling groups may be productive ornonproductive for individual members. They occur primarily because ofcounselor ineptitude arising out of false beliefs regarding the nature ofgroup counseling. Counselors who clearly understand that the group doesnot exist, only each member does, and that interventions must be tailoredto helping each work on his or her concerns and achieve his or her personalcounseling goals, are the ones who will find no difficulty in dealingwith group silence periods. Specific constructive counselor behaviors arepresented for dealing with silence in counseling groups. Group counseloreffectiveness is stressed throughout.